Application of electrochemically activated solution to control pathogens of hydroponic solution - Hai, Nguyen Thi Thanh; Truong Anh Dung; Nguyen Thi Quy (Vietnam Journal of Science and Technology, 2023)
In the current integration trend, high-tech agriculture is an inevitable direction for agricultural developing countries. In particular, hydroponics is a commonly used farming technique due to many advantages: no soil, space saving, no weeds, easy control of influencing factors, double yield. Hydroponic crop production systems are used worldwide to grow flowers, foliage, litter, and fruit and vegetable crops. Like other farming methods, hydroponics still has problems with pests and diseases that cause serious damage to the harvest that have not been completely resolved. One of the sources of pathogens is the hydroponic solution. Many methods to kill bacteria and fungi in hydroponic solutions have been studied. However, some methods gave low efficiency, others gave high efficiency but it caused secondary environmental pollution. Electrochemical activated solution (EAS), produced from dilute sodium chloride (NaCl) solution, has been wide known as a super disinfectant solution with high ability to kill most bacteria and fungi and is safe for humans. In this study we were forced on determine the ability to control pathogens in hydroponic solution of EAS, the effects of EAS on hydroponic solution properties and the growth of Brassica juncea in the mixed of EAS – hydroponic solution. Difference volume of EAS were added into hydroponic solutions and mixed for 30, 45, 60, 120 or 180 min. The most effective mixed solution (mixed ratio and time) was selected to apply to cultivate Brassica juncea. The results show that EAS has the ability to control pathogens in hydroponic solution very effectively, replacing other harmful chemicals. When increasing the volume EAS added (higher ACC of mixed solution) or the exposure time the TDS and ORP index of hydroponic solution were raised slightly while pH value was slightly dropped and the total coliform counts decreased significantly. The total coliform counts of mixed solutions reduced over the exposed time. However, the increasing rate of killing ability of EAS was decreased (along with ACC of solutions). Meanwhile, there was no obvious change in the nitrate concentration. The most effective mixed ratio EAS: hydroponic solution and exposure time for pathogens control were 2.5:500 with 30 min or 1.5:500 with 90 min. The mixed ratio of 1.5:500 with 90 min of exposure time were recommended because of its lesser changes on the properties of hydroponic solution. The mixed EAS - hydroponic solution did no negative effect to the growth of Brassica juncea in comparison with original hydroponic solution.